2010
DOI: 10.1080/10888705.2010.507119
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Electrical Water-Bath Stun Systems for Poultry Slaughter and Recent Developments in Alternative Technologies

Abstract: Prior to slaughter, most farmed birds move through a constant-voltage, multiple-bird, electrical water-bath stun system. Using this system subjects live birds to stressful and painful shackling, and the potential exists for them to receive prestun electric shocks and induction of seizures while still conscious. The existing electrical water-bath stunner settings, particularly those used in U.S. slaughter plants, are not necessarily based on sound scientific data that they produce a consistent, immediate stun, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…As noted by others, 48,49 further research is needed to evaluate the effectiveness and humaneness of electrical stunning with low-voltage settings in 1-and 2-phase stunning systems. Contradicting this, another research group evaluating a similar 2-phase step-up stunner (phase one, 23 V [550 Hz direct current for 10 seconds]; phase two, 15 V [60 Hz alternating current for 5 seconds]) found that the poststunning EEG had a brief period of high-amplitude spikes that progressively decreased in amplitude over time.…”
Section: Physiologic Reactionsmentioning
confidence: 93%
“…As noted by others, 48,49 further research is needed to evaluate the effectiveness and humaneness of electrical stunning with low-voltage settings in 1-and 2-phase stunning systems. Contradicting this, another research group evaluating a similar 2-phase step-up stunner (phase one, 23 V [550 Hz direct current for 10 seconds]; phase two, 15 V [60 Hz alternating current for 5 seconds]) found that the poststunning EEG had a brief period of high-amplitude spikes that progressively decreased in amplitude over time.…”
Section: Physiologic Reactionsmentioning
confidence: 93%
“…Some birds touch this water with their wings first, which results in their sustaining small electric shocks before being stunned. Research has shown that many birds are not stunned effectively and that they therefore either recover consciousness or do not lose consciousness before the next stage (Shields et al 2010). It has also been found that some birds are stunned inappropriately by the process taking place too slowly.…”
Section: The Lives Of Chickensmentioning
confidence: 99%
“…Their feet and heads are then cut off, and they are eviscerated. Finally, they are packed for sale (Shields et al 2010). As many of these processes inflict pain on these animals, some have suggested that alternative systems should be developed; one of these alternative systems could be 'controlled atmosphere killing' , a method that uses gas to render birds unconscious, but it has been remarked that many slaughterhouses may find this system 'too expensive to implement' (Lines et al 2011, 129).…”
Section: The Lives Of Chickensmentioning
confidence: 99%
“…It is likely that such wing flapping could lead to dislocated joints and/or broken bones; this has not been quantified. However, it has been shown that these vigorous movements can lead to haemorrhages of the wing tip (Shields and Raj, ,b).…”
Section: Assessmentmentioning
confidence: 99%